Advancements in the use of 24-hour impedance-pH monitoring for GERD diagnosis. (August 2022) - Marabotto, Elisa; Savarino, Vincenzo; Ghisa, Matteo; Frazzoni, Marzio; Ribolsi, Mentore; Barberio, Brigida; Savarino, Edoardo
Abstract: Gastro-esophageal reflux disease (GERD) occurs in about 25% of the general population. The complexity of the disease and the multiplicity of its clinical manifestations impair the availability of a singular diagnostic test. The majority of GERD patients do not have any endoscopically visible lesions, the so-called non-erosive reflux disease (NERD). This latter population consists of several subgroups characterized by: 1. excess of acid; 2. normal acid, but hypersensitivity to acid or weakly acidic reflux; 3. normal acid, but lack of any relationship between symptoms and reflux episodes. At present, 24-h impedance-pH monitoring represents the best diagnostic tool to detect abnormal reflux and to correlate symptoms to reflux episodes. Moreover, the recent adoption of novel impedance metrics, such as mean nocturnal baseline impedance and post-reflux swallow-induced peristaltic wave index, seem to be able to improve the diagnostic yield of 24-h impedance-pH monitoring, making this test the most accurate in diagnosis of GERD.